Элементный состав Valeriana officinalis L. - Глухов, А.З.; Остапко, И.Н.; Купенко, Н.П. (Промышленная ботаника, 2003)
Element composition of Valeriana officinalis L. above-ground part and roots of the named plant, having been grown in the Donetsk botanical gardens, Nat. Acad. Sci. of Ukraine has been examined. An unsignificant exceeding of sanitary standards as for Zn, Pb, Cr accumulation, with exclusion of Fe and Cd, has been fixed. The data obtained are important for characterizing specifics of 29 chemical elements accumulation in V. officinalis in the region.